2002
DOI: 10.1017/s1121189x00005686
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological and neuropsychiatric perspectives on maternal cradling preferences

Abstract: Objective -To assess competing explanations for the universal preference of mothers to cradle infants on their left side and to propose a relation to hemispheric asymmetry for social attachment and communication behaviour. Methods -A review of observational, experimental, physiological, psychological, neuro-physiological, and neuro-psychological studies, including new findings on the cradling behaviour of mothers with auditory or visual impairments. Results -A significant leftcradling bias is observed in both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 40 publications
1
20
0
Order By: Relevance
“…More left-than right-holders also have been found to show left-biased attention for emotional sounds, namely a left-ear (right hemisphere) advantage for perceiving emotional tone in dichotically presented words (Almerigi, Van Hooren, Bulman-Fleming, & Harris, 2002b) and sentences (Donnot, 2007). Sieratzki and Woll (1996) have proposed that vocal exchanges have primacy over visual exchanges in the motherÁinfant relationship (e.g., Fifer & Moon, 1994), consistent, as they also noted (Sieratzki & Woll, 2002), with the results of a study by Reissland (2000) that analysed mothers' vocalisations while they cradled their infants on either side. Their vocalisations changed in emotional tone depending on the side, being low-pitched and presumably soothing when they held on the left, and high-pitched and presumably exciting when they held on the right.…”
Section: Sex Of Holdermentioning
confidence: 97%
“…More left-than right-holders also have been found to show left-biased attention for emotional sounds, namely a left-ear (right hemisphere) advantage for perceiving emotional tone in dichotically presented words (Almerigi, Van Hooren, Bulman-Fleming, & Harris, 2002b) and sentences (Donnot, 2007). Sieratzki and Woll (1996) have proposed that vocal exchanges have primacy over visual exchanges in the motherÁinfant relationship (e.g., Fifer & Moon, 1994), consistent, as they also noted (Sieratzki & Woll, 2002), with the results of a study by Reissland (2000) that analysed mothers' vocalisations while they cradled their infants on either side. Their vocalisations changed in emotional tone depending on the side, being low-pitched and presumably soothing when they held on the left, and high-pitched and presumably exciting when they held on the right.…”
Section: Sex Of Holdermentioning
confidence: 97%
“…It appears that babies expect to be kept in close physical contact with their mother, being carried for most of the day. Carrying a baby provides proprioceptive‐vestibular stimulation, which encourages neonatal alertness, and an environment within which interaction between caregiver and child is easily facilitated (Gregg, Haffner, & Korner, 1976; Lozoff, Brittenham, Trause, Kennell, & Klaus, 1977; Sieratzki & Woll, 2002). Thus, encouraging mothers to carry their baby results in increased maternal responsiveness and security of attachment (Anisfeld, Casper, Nozyce, & Cunningham, 1990).…”
Section: Physiologically Congruent Care For Infantsmentioning
confidence: 99%
“…Based on research demonstrating right hemisphere asymmetries in emotional monitoring (e.g., Campbell, 1982;Leventhal & Tomarken, 1986), Manning and Chamberlain (1991) suggested that the mother was better able to monitor her infant's well-being in her left visual field and with her left ear because they project more directly to the right hemisphere. If the control of emotions is implicated in the determination of left-holding side preferences, the most valid procedure would certainly be a real situation of interactions among mother-infant pairs (Sieratzki & Woll, 2002).…”
mentioning
confidence: 99%